KUALITAS PELAYANAN PUBLIK PADA WILAYAH KONFLIK TAPAL BATAS - Febri Yuliani, Ilham Refner, Sujianto, (Jurnal Ilmu Administrasi Negara, 2020)
The purpose of this study was to determine the quality of public services at the Kunto darussalam sub-district office towards the people of the border areas of Rokan Hulu Regency and Kampar Regency, in accordance with the 2005 governor's regulation No.30 regarding affirmation of administrative areas of the village administration of Diamond Village, flat land, Diamond Jaya, rimbo makmur, included in the administrative region of kunto Darussalam sub-district, rokan hulu district. And what are the effects. The theory in this study uses the theory from Tjiptono in Hardiyansyah about the quality of public services. This research was conducted using qualitative descriptive methods. The sampling technique used was Purposive Sampling, with data collection using the method of observation, interviews and documentation. The results of this study showed that the quality of public services at the Kunto darussalam sub-district office towards the people of the border region of Rokan Hulu and Kampar districts. did not go as expected, and there are still constraints in facilities and infrastructure as well as the budget. In addition, it was also concluded that due to the pros and cons of fighting over the administrative area, it affects the community, and causes conflict between communities and its impact is generally seen in the community environment.